Dynamics of the Mathematical Model Related to COVID-19 Pandemic with Treatment: Özlem Ak Gumus, A. George Maria Selvam, Rajendran Janagaraj - Team, Support (Thai Journal of Mathematics, 2022)
COVID-19, declared as a pandemic worldwide, has different effects on people. Although there is still nospecific vaccine or a single type of treatment for this disease, it is known that various treatment methods are usedfor this disease. This study is based on the idea that, contrary to the claims that herd immunity against COVID-19can be achieved, most patients who respond to treatment may also lose immunity after recovery. To analyze thedynamic behavior of COVID-19 with a mathematical model, a new modified SIRS model with a treatment functionis considered. Findings show that the disease presents a situation that leads to chaos.